Dynamics of Changes in the Level of Competitiveness of Manufacturing in Poland - Roszko-Wójtowicz, Elżbieta (Studia Miejskie, 2020)
The development of modern economies is inseparably connected with the phenomenon of competition and competitiveness of business entities. Issues in the field of competitiveness of economies, sectors and enterprises have become the subject of intensive analysis worldwide. In Poland, there is also an urgent need to conduct research on various aspects of competitiveness which should thoroughly diagnose the situation in this respect and indicate the development of adequate instruments of economic policy stimulating the growth of competitiveness. This article is a response to this need. The main aim of the study is to assess and compare selected aspects of competitiveness of enterprises from manufacturing divisions. Therefore, the analysis covered manufacturing enterprises (Section C) at the two-digit level of aggregation, i.e. at the level of divisions in this Section. To assess competitiveness in the years 2010-2016, the following measures were used: export/import ratio, intra-industrial trade index (IIT), sold production, labour productivity, and total factor productivity (TFP). The research proceedings were based on data published by the Central Statistical Office (Statistics Poland).